Organización Contable en el comercial del señor Bernal Segarra Rolando Vinicio de la ciudad de Loja, Periodo octubre a diciembre del 2023. - Tandazo Torres, Erick Alexander (2024)
The current Curricular Integration Work, titled "Accounting Organization in the Commercial Enterprise of Mr. Bernal Segarra Rolando Vinicio in Loja City, for the Period of October to December 2023," was conducted to meet the company's needs by gathering, organizing, and recording all relevant commercial transaction data. This effort aimed to provide accurate information about the company's financial and economic status, adhering to the specific objectives set forth. To achieve the first objective, a tailored plan and accounting manual were developed, detailing the company's assets, liabilities, equity, income, costs, and expenses, complete with descriptions and codes to facilitate account identification during the accounting process. Auxiliary records were created to document all transactions, including purchases, sales, accounts receivable and payable, and payroll. This was done to simplify and streamline access to information generated by each operation. The accounting process utilized a perpetual inventory control system to record merchandise movements in Kardex cards. The initial inventory was taken on October 1, 2023, followed by the preparation of the Initial Situation Statement, which documented all assets, liabilities, and rights. Transactions were recorded in the Daily Book and balances in the General Ledger. Subsequently, the Trial Balance, Work Sheet with adjustments, and Comprehensive Income Statement (including income, costs, and expenses) were prepared to determine the final profit. The Financial Position Statement, listing asset, liability, and equity accounts, was created to reflect the company's economic and financial status at the end of the period. Finally, the Cash Flow Statement was prepared to represent the money generated and used during the economic period.